Effect of Acetamiprid, a Neonicotinoid Insecticide, on Locomotor Activity of the American Cockroach - Emiliane Taillebois; Alison Cartereau; Steeve H. Thany (Insects, 2024)
Toxicological studies have shown that the American cockroach Periplaneta americana (Linnaeus) is a classical model for studying the mode of action of commonly used insecticides. In a previous study, we demonstrated that thiamethoxam and clothianidin decreased locomotor activity in an open-field-like apparatus. Here, we tested the effect of the neonicotinoid acetamiprid when applied orally, topically, or injected into the haemolymph. We found that acetamiprid was also able to impair locomotor activity in the open-field-like apparatus. When treated with acetamiprid, a strong alteration in locomotor activity was observed 1 h, 24 h, and 48 h after haemolymph and topical applications. Oral application induced an impairment of locomotor activity at 24 h and 48 h. A comparison of the present data with our previously published results showed that neonicotinoids were more active when injected into the haemolymph compared to oral and topical applications. These findings increased our understanding of the effect of neonicotinoid insecticides on insect locomotor activity, and demonstrated that the cyano-substituted neonicotinoid, acetamiprid, was able to alter cockroach locomotor activity.